"Normally I Try and Capture a Moment, and With This I Had to Create a Moment": Implications of Anonymous Photography Protocols in Photovoice Research with People Who Inject Drugs. (February 2021) - Carlberg-Racich, Suzanne
Photovoice collaborations are designed to promote critical consciousness and advocate for change. People who inject drugs (PWID) are systematically silenced from advocacy for fear of being "outed." Photovoice protocols that prohibit identifying photography provide a safer alternative; however, it is not known how these protections affect participant experience. This study examined how human subjects' protections affect PWID experience in a Photovoice research project. A purposeful sample of PWID ( N = 25) was recruited from a Photovoice study and engaged in semi-structured interviews. Interview transcripts were coded and analyzed for key themes. The majority of participants understood the protections while also explaining the difficulty in achieving their vision. Creativity played a significant role in overcoming the restrictions. A vocal minority voiced strong objections to the restrictive protocol. Allowing only anonymous photography posed certain challenges, but PWID valued the inherent privacy. Creative approaches may aid in overcoming restraints and achieving a balance.